Conservation Consequences of Corallivore Gastropod Predation on Plexaurella grandiflora (Cnidaria: Octocorallia) Populations in Tropical Reefs - Dias Avelino, Camile; Mota, Ellori Laíse Silva; Gondim, Anne Isabelley; Alves, Rômulo Romeu Nóbrega; Dias, Thelma Lúcia Pereira (Ethnobiology and Conservation, 2024)
Octocorals are extremely important animals for forming coral reefs and maintaining life in the marine environment and are widely distributed. The focus species Plexaurella grandiflora is an endemic species from Brazil. It is subject to the most varied external stressors, from ocean surface warming, pollution, damage caused by tourism, and predation by other animals. In this sense, the present study aimed to survey the population characteristics of P. grandiflora in a shallow tropical reef where it occurs in the Northeast of Brazil. Furthermore, we evaluated the stress and damage caused by coral-eating gastropods of the Muricidae family, found associated with colony structure. Through free dives between the years 2016 and 2017, 143 colonies of P. grandiflora were marked and observed, and they were analyzed in their size, supporting substrate, distribution, presence of damage, and impact by coral-eating gastropods. The cataloged colonies were larger than those recognized in the literature and were distributed in aggregate. A total of 85 gastropods of two species (Coralliophila aberrans and Coralliophila salebrosa) were recorded preying on gorgonians. The damage ranged from light to deep, from polyp removal to exposure of the protein axis. Predation occurred predominantly at the base of the colonies. As it is an endemic species and in need of studies, this study warns of the need for studies focused on the ecology and conservation of this gorgonian and its critical habitats.